2021
DOI: 10.1016/s2213-2600(20)30527-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the characteristics, morbidity, and mortality of COVID-19 and seasonal influenza: a nationwide, population-based retrospective cohort study

Abstract: Background To date, influenza epidemics have been considered suitable for use as a model for the COVID-19 epidemic, given that they are respiratory diseases with similar modes of transmission. However, data directly comparing the two diseases are scarce.Methods We did a nationwide retrospective cohort study using the French national administrative database (PMSI), which includes discharge summaries for all hospital admissions in France. All patients hospitalised for COVID-19 from March 1 to April 30, 2020, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

67
483
5
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(564 citation statements)
references
References 30 publications
67
483
5
9
Order By: Relevance
“…Covariates were selected a priori based on previously reported RESEARCH associations with mortality in COVID-19. 10,[41][42][43] Poisson regression 44 was used for models of mortality, readmission and ICU admission to provide risk ratios and avoid misinterpretation of odds ratios obtained from logistic regression. Negative binomial regression was used for models of hospital length of stay and ICU length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates were selected a priori based on previously reported RESEARCH associations with mortality in COVID-19. 10,[41][42][43] Poisson regression 44 was used for models of mortality, readmission and ICU admission to provide risk ratios and avoid misinterpretation of odds ratios obtained from logistic regression. Negative binomial regression was used for models of hospital length of stay and ICU length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as the pandemic death toll rose, some have wondered whether focusing on individual victims could help people better appreciate the threat of the COVID19 pandemic and comply with public health recommendations (Beard, 2020;Graham, 2020;Lewis, 2020). Also, some leaders compared COVID19 to seasonal flus in 2020 despite their public health officials explaining that COVID19 is caused by a different virus, spreads more easily, has a longer period of contagion, causes more serious illness, and is not yet preventable via vaccination (CDC, 2020;Piroth et al, 2020). Some worry that such comparisons to the flu decreased public health compliance and thereby increased COVID19 deaths (Brooks, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent large French retrospective cohort study found that the prevalence of MI and atrial fibrillation was lower in patients with COVID-19 than seasonal influenza with a prevalence of 0.6% vs. 1.1% and 12.4% vs. 15.8% respectively. 7 Unfortunately, this study did not report the prevalence of any other cardiac complications, including heart failure and myocarditis. As cardiomyocytes express ACE2 28,29 , the docking receptor of SARS-CoV-2, it has been speculated that SARS-CoV-2 may infect cardiomyocytes, replicate in cardiac tissue and thereby induce direct myocardial damage.…”
Section: Discussionmentioning
confidence: 88%
“…Coronavirus disease 2019 (COVID-19) has rapidly spread across the globe since December 2019, leading to more than 115 million confirmed cases and 2.5 million fatalities as of the 4 th of March 2021. 1 Although the disease is not as lethal (case fatality ratio (CFR) ∼0.3 – 1%) 2,3 as the Middle-East respiratory syndrome (MERS; CFR ∼35%) 4 and the severe acute respiratory syndrome (SARS; CFR 14 – 15%) 5 , it has become clear that morbidity and mortality is much higher than pandemic influenza (CFR 0.1%) 6,7 , especially among the elderly 3 .…”
Section: Introductionmentioning
confidence: 99%